Technological innovations in mechanical engineering sector in Vietnam: actual status and solutions - Hieu, Nguyen Trong; Hieu, Pham Ngoc; Phi, Nguyen Truong; Xuyen, Nguyen Huu (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Mechanical engineering sector holds the important position in supply chains of parts, components, machines, equipment and production materials. This sector is also the driving forces for development of numerous sectors in the society. Actually, however, mechanical engineering sector is evaluated as low developed despite priorities offered by the State for development. One of main reasons of that is the small segmented and non-integrated activities of technological innovations in the sector. Also the selection of development models and road maps for technological innovations is not clearly conceived then leads to low effectiveness of activities. This study targets to clarify the actual status of technologies and innovations in mechanical engineering sector, and then, on this basis, proposes solutions to promote activities of technological innovations in mechanical engineering sector in lines with the actual conditions in Vietnam. Code: 15081101